Pengaruh Pendidikan Kewirausahaan, “Financial Management “dan Mental Kewirausahaan Terhadap Minat Mahasiswa Berwirausaha: Pengaruh Pendidikan Kewirausahaan, “Financial Management “dan Mental Kewirausahaan Terhadap Minat Mahasiswa Berwirausaha - Trisnadewi, Ni Kadek Ayu; Parma, I Putu Gede (UNHI Press, 2025)
ABSTRAC The purpose of this study was to determine the effect of entrepreneurship education, Financial Management and entrepreneurial mentality on students' interest in entrepreneurship, both partially and simultaneously. This study was conducted at STIE Satya Dharma Singaraja. The data collection technique used a questionnaire. Respondents taken in this study were students of STIE Satya Dharma Singaraja, management study program. The number of samples in this study was 89 people. The data analysis technique used multiple linear regression, determination coefficient test, hypothesis testing with the F test and t test. The results of the study found that entrepreneurship education, Financial Management and entrepreneurial mentality together had a significant effect on interest in entrepreneurship. The sig value of the influence of entrepreneurship education on entrepreneurial interest is 0.006, which is smaller than the ? value of 0.05, so Ho is rejected and Ha is accepted. This means that statistically at ? = 5%, entrepreneurship education has a real (significant) effect on entrepreneurial interest. The sig value of the influence of Financial Management on entrepreneurial interest is 0.018, which is smaller than the ? value of 0.05, so Ho is rejected and Ha is accepted. This means that statistically at ? = 5%, Financial Management has a real (significant) effect on entrepreneurial interest. The sig value of the influence of entrepreneurial mentality on entrepreneurial interest is 0.000, which is smaller than the ? value of 0.05, so Ho is rejected and Ha is accepted. This means that statistically at ? = 5%, entrepreneurial mentality has a real (significant) effect on entrepreneurial interest in STIE Satya Dharma Singaraja students.